“Am I matter for others?” A study on mattering among students in a public university - Yeo, Francis Wee Cheat; Lau, Poh Li (Penerbit Universiti Kebangsaan Malaysia, 2020)
University mattering is a type of societal mattering where students feel they matter when the people in a university knows about them, when the people reacts to their requirements, and when students can make a positive contribution to others. According to Rosenberg and McCullough (1981), mattering consists of four distinct elements which include awareness, importance, reliance, and ego-extension. Mattering had not much local study and it’s not very popular across the local research. Thus, the researcher decided to conduct this study to access university mattering. This study is designed to investigate the level of mattering among public university students. By using the Revised University Mattering Scale (RUMS) to measure the mattering level of 214 respondent. Descriptive analysis and inferential analysis are utilized in the process of analysis of the data. The result shows the overall level of mattering among university students are above average. In addition, the level of mattering among females are slightly higher than males, and the undergraduates’ mattering level is higher than the postgraduates. These findings are consistent with the results of the previous study.